آزادئ اظہاراورمذہبی حساسیت:بین الاقوامی انسانی حقوق اوراسلامی تعلیمات کاتقابلی جائزہ : FREEDOM OF EXPRESSION AND RELIGIOUS SENSITIVITY: A COMPARATIVE REVIEW OF INTERNATIONAL HUMAN RIGHTS AND ISLAMIC TEACHINGS (Al-Aasar, 2026)
Every person on earth is connected to some belief or another, and in some cases, this connection reaches the point of obsession. Given the sensitivity of religion, opinions about it should be expressed carefully, ensuring that the religious and spiritual sentiments of others are not hurt. In this context, where freedom of expression is a fundamental democratic right, what are its limits? And under what circumstances is the expression of opinion considered valid? All these matters constitute a highly sensitive topic. Therefore, the study discussed the definition and limitation of freedom of expression, as well as their legal and social status, in addition to the issues of religious sensitivity in which their legal status was explained. The study examines the status of religious freedom and rights in the Universal Charter of Human Rights and how international human rights organisations have developed and interpreted religious law.